Current Considerations in Direct Percutaneous Endoscopic Jejunostomy - Yanfei Zhu; Liping Shi; Hao Tang; Guoqing Tao (Canadian Journal of Gastroenterology)
For patients who are unable to meet their nutritional needs orally, enteral feeding via a percutaneous approach has become the mainstay of therapy. However, traditional enteral feeding methods, such as percutaneous endoscopic gastrostomy, may not be viable options for patients with severe gastroparesis or gastric outlet obstruction. Direct percutaneous endoscopic jejunostomy (DPEJ) is an enteral access method that was first described more than 20 years ago and has gained popularity among gastroenterologists. This review discusses the indications for and contraindications to DPEJ, the procedure, the application of DPEJ in specific subsets of patients with gastrointestinal disorders, and presents a brief tabular summary of complications and success rates of DPEJ in case series published since 2000.